Predictors of mortality in extramural very low birth weight neonates: a prospective observational study - Meshram, Rajkumar M.; Gedam, Ruchi A.; Garg, Shivangi; Kadu, Kalyani S.; Chakraborty, Madhabika R.; Kumar, Swaroop B. (International Journal of Contemporary Pediatrics, 2020)
Background: Over the past few decades, the burdens of very low birth weight (VLBW) preterm infants are increasing due to advances in obstetrics and perinatal services. Objectives of the study were to assess predictors of mortality of extramural VLBW neonates. Methods: Prospective one year cohort study was undertaken on VLBW neonates fulfilling the inclusion criteria at a tertiary institute. Maternal and neonatal demographic data were analyzed. Results: Male to female ratio was 1.26:1. One hundred and thirty seven (74.9%) neonates had birth weights from 1000-1499 g while 46 (25.1%) had birth weights <1000 g (ELBW) and 90% were preterm. One hundred and sixty five (90.2%) neonates were admitted in early neonatal period. Anaemia was the commonest maternal illness and preeclampsia/eclampsia was the most common obstetric complication. Respiratory distress, temperature instability and lethargy were common clinical presentations. Respiratory distress, sepsis and perinatal asphyxia were common diagnoses on admission. Mortality rate in VLBW neonates was 59.6% and respiratory distress was the commonest cause of death. Male gender (p=0.01), home delivery (p=0.04), vaginal delivery (p=0.05) and positive septic screen (p=0.003) had significantly higher mortality while mode of delivery (aOR 0.27 CI 0.086-0.83 p=0.02) and positive septic screen (aOR 4.0 CI 1.67-9.84 p=0.002) were independent risk factors for mortality. Conclusions: In extramural VLBW neonates, male gender, home delivery, vaginal delivery and positive septic screen had significantly higher mortality whilst mode of delivery and positive septic screen were independent risk factors for mortality.